2020
DOI: 10.3390/jcm9020452
|View full text |Cite
|
Sign up to set email alerts
|

Pain Predictors in a Population of Temporomandibular Disorders Patients

Abstract: The aim of the present study was to assess the potential role of some biological, psychological, and social factors to predict the presence of painful temporomandibular disorders (TMDs) in a TMD-patient population. The study sample consisted of 109 consecutive adult patients (81.7% females; mean age 33.2 ± 14.7 years) who were split into two groups based on Research Diagnostic Criteria for Temporomandibular Disorders (RDC/TMD) diagnoses: painful TMD and non-painful TMD. The presence of pain was adopted as the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
37
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 27 publications
1
37
0
1
Order By: Relevance
“…Greater pain intensity, longer duration of pain, persistent pain, impaired social functioning, and the likelihood of poor treatment outcome are seen when depression and pain coexist [ 48 ]. A similar study assessing the potential role of biological, psychological, and social factors in order to predict the presence of painful TMD using multivariate analysis found a relationship between TMD pain and depression, which supports the need of considering both psychological factors in relation to TMD signs and symptoms [ 27 ].…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Greater pain intensity, longer duration of pain, persistent pain, impaired social functioning, and the likelihood of poor treatment outcome are seen when depression and pain coexist [ 48 ]. A similar study assessing the potential role of biological, psychological, and social factors in order to predict the presence of painful TMD using multivariate analysis found a relationship between TMD pain and depression, which supports the need of considering both psychological factors in relation to TMD signs and symptoms [ 27 ].…”
Section: Discussionmentioning
confidence: 69%
“…Decreased PPT and higher scorings for psychological factors in TMD patients compared to healthy controls are well known in the literature [ 5 , 14 , 15 , 21 , 27 , 32 , 41 , 42 ], but the relationship of different factors with predicting TMD patients is yet to be described. To our knowledge, this study is the first to analyse the interrelationship between experimental pain thresholds and psychometric variables in relation to TMD by using a multivariate regression model.…”
Section: Discussionmentioning
confidence: 99%
“…Temporomandibular disorders (TMD) refer to a set of conditions affecting masticatory muscles and the temporomandibular joints. The impact of stressful events on the occurrence and worsening of TMD symptoms is not completely clear but evidence shows a strong connection between the two (Auerbach, Laskin, Frantsve, & Orr, 2001; Canales, Guarda‐Nardini, Rizzatti‐Barbosa, Conti, & Manfredini, 2019; Osiewicz, Lobbezoo, Ciapała, Pytko‐Polończyk, & Manfredini, 2020), with more numerous and/or frequent somatic, psychologic, and behavioral symptoms of stress in TMD patients when compared to control (Beaton, Egan, Nakagawa‐Kogan, & Morrison, 1991; Jivnani et al., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…So far, several studies have assessed the different factors from different domains as predictors for the pain-related outcomes in TMDs. For example, Osiewicz et al [ 41 ] assessed the association of biological, psychological, and social factors with the presence of painful TMDs, and found that depression was the most important predictor for the presence of painful TMD. Banafa et al [ 42 ] assessed the association of socio-demographic background and denture status at baseline with TMJ pain and masticatory muscles pain on palpation after 11-year follow-up in Finnish adult population, and found that all the predictors, including gender and age, were not significantly associated with the presence of TMJ pain at follow-up.…”
Section: Discussionmentioning
confidence: 99%